Mutation in BMPR2 promoter: a ‘second hit’ for manifestation of pulmonary arterial hypertension? - Rodríguez Viales, Rebecca; Eichstaedt, Christina; Benjamin, Nicola; Fischer, Christine; Lichtblau, Mona; Grünig, Ekkehard; Hinderhofer, Katrin (PLOS ONE, 2015)
Background Hereditary pulmonary arterial hypertension (HPAH) can be caused by autosomal dominant inherited mutations of TGF-β genes, such as the bone morphogenetic protein receptor 2 (BMPR2) and Endoglin (ENG) gene. Additional modifier genes may play a role in disease manifestation and severity. In this study we prospectively assessed two families with known BMPR2 or ENG mutations clinically and genetically and screened for a second mutation in the BMPR2 promoter region. Methods We investigated the BMPR2 promoter region by direct sequencing in two index-patients with invasively confirmed diagnosis of HPAH, carrying a mutation in the BMPR2 and ENG gene, respectively. Sixteen family members have been assessed clinically by non-invasive methods and genetically by direct sequencing. Results In both index patients with a primary BMPR2 deletion (exon 2 and 3) and Endoglin missense variant (c.1633G>A, p.(G545S)), respectively, we detected a second mutation (c.-669G>A) in the promoter region of the BMPR2 gene. The index patients with 2 mutations/variants were clinically severely affected at early age, whereas further family members with only one mutation had no manifest HPAH. Conclusion The finding of this study supports the hypothesis that additional mutations may lead to an early and severe manifestation of HPAH. This study shows for the first time that in the regulatory region of the BMPR2 gene the promoter may be important for disease penetrance. Further studies are needed to assess the incidence and clinical relevance of mutations of the BMPR2 promoter region in a larger patient cohort.
Gesehen am 22.03.2017